The Effect of Different Phases of Synchrony on Pain Threshold in a Drumming Task - Sullivan, Philip; Blacker, Mishka (Frontiers in Psychology, 2017)
Behavioural synchrony has been linked to endorphin activity (Cohen et al., 2010; Sullivan & Rickers, 2013; Sullivan et al. 2014; Tarr et al, 2015; 2016; Weinstein et al., 2016). This has been called the synchrony effect. Synchrony has two dominant phases of movement; in-phase and anti-phase. The majority of research investigating synchrony’s effect on endorphin activity has focused on in-phase synchrony following vigorous activities. The only research to investigate the effects of anti-phase synchrony on endorphin activity found that anti-phase synchronized rowing did not produce the synchrony effect (Sullivan et al., 2014). Anti-phase synchrony, however, is counter-intuitive to the sport of rowing and may have interfered with the synchrony effect. This study investigated the effect of anti-phase synchrony on endorphin activity in a different task (i.e., drumming). University students (n=30) were asked to drum solo and in in-phase and anti-phase pairs for three minutes. Pain threshold was assessed as an indirect indicator of endorphin activity prior to and following the task. Although the in-phase synchrony effect was not found, a repeated measures ANOVA found that there was a significant difference in pain threshold change among the three conditions (F (2, 24) = 4.10, η2 = .255 p < .05). Post hoc t tests showed that the anti-phase condition had a significantly greater pain threshold change than both the solo and in-phase conditions at p < .05. This is the first time that anti-phase synchrony has been shown to produce the synchrony effect Because anti-phase drumming may have required more attention between partners than in-phase synchrony, it may have affected self-other merging (Tarr et al., 2014). These results support Tarr et al.’s (2014) model that multiple mechanisms account for the effect of synchrony on pain threshold, and suggest that different characteristics of the activity may influence the synchrony effect.